A photothermal-electric heating deicing film based on recovery of nanometer copper sulfide from waste copper etching solution
Patent Information
- Application Number
- CN202611033883.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-13
AI Technical Summary
例如公开号为CN121377192A的一种基于面板行业铜蚀刻废液的高效回收再利用工艺,采用萃取反萃取
电解工艺回收单质铜,但流程冗长,有机萃取剂易损耗残留,电解能耗高且受废液中有机物干扰
本发明中,纳米硫化铜因其局域表面等离激元共振效应以及半导体带间的非辐射弛豫复合,实现了全太阳光谱的宽波段吸收和高的光热转换能力。同时,硫化铜薄膜优良的导电性能使其能够在低功率条件下实现快速、均匀的电加热功能。由此制备得到的纳米硫化铜薄膜将光热与电热两种功能集成于同一除冰膜中,解决了传统光热除冰膜在光照不足时失效的问题,实现了全天候除冰。并且本发明是利用显示面板行业铜制程产生的废刻蚀液制备纳米硫化铜除冰膜,工艺简单,实现了废液的资源化利用,显著降低了除冰膜的制造成本。
Smart Images

Figure CN122534707B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of energy conservation and environmental protection technology, and to the high-value utilization of waste liquid generated in industries such as display panels. Specifically, it relates to a photothermal-electrothermal de-icing film based on the recovery of nano-copper sulfide from waste copper etching solution. Background Technology
[0002] Icing is a common natural phenomenon, but it has significant negative impacts on various industries, including aviation, power, transportation, and shipping, sometimes even causing personal injury and property damage. Traditional de-icing technologies are mainly divided into two categories: chemical and physical methods. Chemical de-icing (especially chloride-based de-icing agents) has drawbacks such as easy corrosion of metal workpieces and significant environmental hazards; while physical de-icing (such as mechanical de-icing) is easily limited by the working environment and suffers from high energy consumption and high costs. In recent years, solar energy, as a clean energy source, has received widespread attention for its application in de-icing technology. Photothermal conversion materials absorb sunlight and convert it into heat energy, raising the temperature of the target object and thus achieving the purpose of de-icing. Although some progress has been made in the research of photothermal de-icing coatings, most of them rely on high-cost materials such as metal nanoparticles, graphene, and carbon nanotubes, which limits their engineering application. In addition, photothermal de-icing technology is highly dependent on sunlight conditions; in climatic conditions with insufficient sunlight, such as at night or during consecutive cloudy days, the photothermal coating is difficult to function effectively.
[0003] At the same time, the copper manufacturing process for large-size display panels generates a large amount of waste etching solution, which contains high concentrations of copper ions, chelating agents, and organic pollutants. Direct discharge of such solution wastes copper resources and harms the environment.
[0004] Currently, there are various resource recovery methods, but all have technical limitations. For example, a highly efficient recycling and reuse process for copper etching waste liquid from the panel industry, disclosed in CN121377192A, employs extraction... Back-extraction Electrolysis is used to recover elemental copper, but the process is lengthy, organic extractants are easily lost and left behind, electrolysis has high energy consumption and is affected by organic matter in the waste liquid.
[0005] For example, the method for the complete recovery of acidic copper chloride etching waste liquid by thermal precipitation, disclosed in CN113460965A, recovers sodium chloride and copper chloride through evaporation and stepwise cooling crystallization. However, it does not take into account the differences in the composition of the waste liquid, and the ion concentration fluctuates greatly in actual production, making the process relatively complicated.
[0006] In summary, existing waste copper etching solution treatment processes generally suffer from problems such as lengthy processes, high energy consumption, low product added value, and weak resistance to fluctuations. Therefore, the recycling of waste etching solutions has significant economic and environmental benefits, and developing new high-value, low-energy-consumption treatment processes is an essential path for the optoelectronic industry to achieve energy conservation and environmental protection. Summary of the Invention
[0007] To overcome the problems of high cost, high energy consumption, and poor environmental adaptability of existing de-icing technologies, especially the difficulty of effective photothermal de-icing under weak or no light conditions, this invention provides a photothermal-electrothermal de-icing film based on the recovery of nano-copper sulfide from waste copper etching solution. This de-icing film has low cost, can achieve all-weather de-icing with the synergy of electrothermal and photothermal processes, and is also expected to solve the problem of high-value utilization of waste liquid in copper manufacturing processes in the display panel industry.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A photothermal-electrothermal de-icing membrane for recovering nano-copper sulfide based on waste copper etching solution includes a heating element and electrodes, wherein the heating element is a nano-copper sulfide thin film deposited on the surface of a nylon filter membrane; The electrodes are respectively attached to both sides of the copper sulfide nanofilm, forming an electrical connection with the copper sulfide nanofilm, and the middle region of the copper sulfide nanofilm has an exposed portion for receiving sunlight. A polydimethylsiloxane hydrophobic coating is applied to the upper surface of the nano-copper sulfide film and the upper surface of the nano-copper sulfide film at the contact point with the copper electrode.
[0009] The nano-copper sulfide film utilizes its electrical conductivity and Joule heating effect to achieve electric heating, thereby enabling electrothermal de-icing when an external power source is connected. The photothermal effect of the nano-copper sulfide thin film comes from its local surface plasmon resonance effect and nonradiative relaxation recombination between semiconductor bands, achieving wide-band absorption and high photothermal conversion capability across the entire solar spectrum, thus enabling photothermal de-icing under sunlight. The photothermal-electrothermal de-icing membrane has two functional modes: electrothermal de-icing and photothermal de-icing. It can be operated by selecting one of the functional modes or by operating both functional modes in combination to achieve all-weather de-icing.
[0010] The nano-copper sulfide film is composed of Cu9S8 and Cu 31 S 16 Mixed composition, in which copper element is Cu + / Cu² + Mixed valence states exist; the lattice of the nano-copper sulfide thin film material contains a large number of copper vacancies. In order to maintain overall electroneutrality, some Cu... + Oxidized to Cu² + To compensate for the lack of positive charge, Cu is formed that is rich in copper vacancies. x S-phase. These copper vacancies induce a high concentration of free holes, which oscillate collectively in the photoelectric field, generating a strong localized surface plasmon resonance effect.
[0011] A method for preparing a photothermal-electrothermal de-icing film based on the recovery of nano-copper sulfide from waste copper etching solution includes the following steps: Step 1: Add sodium sulfide solution dropwise to the waste etching solution, stir and let stand to obtain a mixture of reaction products; Step 2: After standing, the upper layer of the mixture is a clear liquid and the lower layer is a suspension; the lower suspension is taken out and diluted with a mixed solvent of deionized water and anhydrous ethanol to obtain a diluted solution; Step 3: Deposit the diluent onto the surface of the nylon filter membrane by vacuum filtration. Add 5-10 mL of diluent each time. After each layer of film is deposited, wash with anhydrous ethanol. After multiple vacuum filtrations and washings, a black film sample is obtained. Step 4: Air-dry the black film sample obtained in Step 3 at room temperature, and then bake it to obtain a nano copper sulfide film. Step 5: Prepare electrodes on both sides of the copper sulfide nanofilm obtained in step 4; Step 6: After shielding and protecting the electrodes on both sides of the nano-copper sulfide film obtained in Step 5, a polydimethylsiloxane coating is sprayed onto the surface of the copper sulfide and then cured. After hydrophobic modification, a photothermal-electrothermal de-icing film of nano-copper sulfide is obtained.
[0012] In step 1, polyethylene glycol dispersant is added to the waste copper etching solution. The copper-containing waste etching solution comes from the copper manufacturing process in the display panel industry.
[0013] In step 1, the sodium sulfide solution is 0.1 g / mL, and the volume ratio of sodium sulfide solution to polyethylene glycol is between 5:1 and 10:1.
[0014] In step 1, the volume ratio of waste etching solution to sodium sulfide solution is between 4:1 and 5:1.
[0015] The dilution factor of the diluent in step 2 is 25 to 50 times.
[0016] In step 3, the nylon filter membrane has a diameter of 50 mm and a pore size of 0.1 μm.
[0017] In step 3, adjusting the filtration process and the number of cycles can control the thickness of the copper sulfide film produced.
[0018] In step 4, the drying temperature is 60–80 °C.
[0019] In step 5, the electrode is made of copper tape.
[0020] In step 6, the polydimethylsiloxane to be sprayed is diluted with ethyl acetate to a mass ratio of 1:3 to 1:4.
[0021] In step 6, the curing temperature is 60-80 ℃ and the curing time is 1-2 h.
[0022] The de-icing membrane is used for de-icing in one or more scenarios, such as aircraft wings, drone supports, wind turbine blades, or ship decks.
[0023] The de-icing membrane is fixed to the surface of the object to be de-iced by attaching, bonding or embedding, and can be selected to work in photothermal mode only, electrothermal mode only or dual-mode collaborative operation according to the usage scenario.
[0024] The beneficial effects of this invention are: In this invention, copper sulfide nanoparticles achieve broad-band absorption across the entire solar spectrum and high photothermal conversion capability due to their localized surface plasmon resonance effect and nonradiative relaxation recombination between semiconductor bands. Simultaneously, the excellent conductivity of the copper sulfide film enables rapid and uniform electrothermal heating under low-power conditions. The resulting copper sulfide nanoparticle film integrates both photothermal and electrothermal functions into a single de-icing film, solving the problem of traditional photothermal de-icing films failing under insufficient light and achieving all-weather de-icing. Furthermore, this invention utilizes waste etching solution generated from copper manufacturing processes in the display panel industry to prepare the copper sulfide nanoparticle de-icing film, simplifying the process, realizing resource utilization of waste liquid, and significantly reducing the manufacturing cost of the de-icing film.
[0025] The nano-copper sulfide de-icing film prepared by this invention has a high concentration of free holes induced by copper vacancies, which endows the material with excellent photothermal and electrothermal properties. It can quickly heat up and de-ic under sunlight or applied voltage, thus effectively adapting to the de-icing needs under variable environmental conditions. Attached Figure Description
[0026] Figure 1 The results of SEM and EDS analysis of the nano-copper sulfide thin film prepared in Example 1 are shown below; Figure 1 (a) shows the surface morphology of the nano-copper sulfide film, revealing the microstructure of the nanoparticles; Figure 1 (b) shows the EDS energy dispersive spectroscopy results of sulfur in the nano-copper sulfide thin film, indicating that sulfur is uniformly distributed inside the film; Figure 1 (c) shows the EDS energy dispersive spectroscopy results of copper in the nano-copper sulfide thin film, indicating that copper is uniformly distributed inside the film.
[0027] Figure 2 The XRD test results are for the nano-copper sulfide thin film obtained in Example 1.
[0028] Figure 3 The absorbance spectrum of the nano-copper sulfide thin film obtained in Example 1 is shown in the range of 250-2500 nm.
[0029] Figure 4 The figure shows the IV curve test results of the nano-copper sulfide de-icing film prepared in Example 1.
[0030] Figure 5 The graph shows the temperature rise curve of the nano-copper sulfide de-icing film obtained in Example 1 under AM1.5G simulated sunlight.
[0031] Figure 6 The graph shows the temperature rise of the nano-copper sulfide de-icing film obtained in Example 1 under the condition of applying a DC voltage of 10-14 V.
[0032] Figure 7 The results of the de-icing function verification of the nano-copper sulfide de-icing film obtained in Example 1 were obtained by freezing 20 microliters of liquid droplets at -30°C and performing photothermal, electrothermal, and synergistic de-icing processes at an ambient temperature of -15°C.
[0033] Figure 8 This is a schematic diagram of the overall structure of the photothermal-electrothermal de-icing film of the present invention. Detailed Implementation
[0034] The present invention will now be described in further detail with reference to the accompanying drawings.
[0035] Example 1: Take approximately 60 mL of waste etching solution (with 2 mL of polyethylene glycol added), and add approximately 15 mL of 0.1 g / mL sodium sulfide solution (with 2 mL of polyethylene glycol added) dropwise while stirring. After the addition is complete, continue stirring for 20 min, then let it stand for 30 min. Take 2 mL of the lower black suspension and dilute it to 50 mL with a 1:1 mixture of deionized water and anhydrous ethanol to obtain the diluted solution.
[0036] A 50 mm diameter nylon filter membrane (0.1 μm pore size) was used with a vacuum filtration device for filtration. 5 mL of diluent was added each time, and after filtration, 5 mL of anhydrous ethanol was added for washing. This filtration and washing process was repeated 5 times to obtain a uniform black film sample. The sample was air-dried at room temperature for 2 h, then transferred to an oven and dried at 60 ℃ for 2 h to obtain a copper sulfide nanofilm.
[0037] The obtained thin film was subjected to SEM, EDS, XRD and absorbance tests to verify its phase and physicochemical properties. The results are as follows: Figure 1 As shown in Figures 2 and 3.
[0038] like Figure 1 As shown, the prepared sample contains Cu and S elements, and the microstructure of copper sulfide is nanoparticles with a particle size of about tens of nanometers and uniform distribution.
[0039] like Figure 2 As shown, nano-copper sulfide is composed of Cu9S8 and Cu 31 S16 Both are mixed compositions and belong to typical non-stoichiometric copper sulfide compounds, in which copper is mainly Cu. + / Cu² + Mixed valence states exist, containing a large number of copper vacancies. These copper vacancies induce a high concentration of free holes, which oscillate collectively in the photoelectric field, generating a strong localized surface plasmon resonance effect.
[0040] like Figure 3 As shown, the nano-copper sulfide film exhibits significant absorption of light in the wavelength range of 250–2500 nm. Among them, there is significant plasmon resonance absorption in the near-infrared band (800–1100 nm), and there is also light absorption caused by interband transitions in the ultraviolet-visible band.
[0041] Copper tapes were attached as electrodes on both sides of the obtained copper sulfide nanofilm, with an electrode width of 10 mm and a spacing of 20 mm between the electrodes. A hydrophobic coating of polydimethylsiloxane (PDMS and ethyl acetate diluted at a mass ratio of 1:4) was uniformly sprayed onto the surface of the copper sulfide film, and then cured at 60 °C for 2 h to complete the encapsulation of the photothermal-electrothermal dual-mode de-icing film.
[0042] The encapsulated de-icing membrane was subjected to IV curve testing, and the results are as follows: Figure 4 As shown, the curve is a straight line passing through the origin, demonstrating the excellent electrical conductivity of the copper sulfide thin film.
[0043] The performance of the nano-copper sulfide de-icing film prepared in this embodiment was tested: the temperature rise curve under AM1.5G simulated sunlight irradiation (light intensity of 1 kW / m²) and the temperature rise curve of the copper sulfide de-icing film under the condition of applying a DC voltage of 10-14 V are shown in the figure. Figure 5 , 6 As shown.
[0044] like Figure 5 As shown, the temperature of the de-icing film increased from 25 °C to 59.2 °C within 600 s, demonstrating excellent photothermal conversion performance.
[0045] like Figure 6 As shown, the temperature of the de-icing film increased significantly within 120 seconds under different DC voltage conditions. Furthermore, at 14 V, the temperature reached 46.3 °C, demonstrating excellent electrothermal conversion performance.
[0046] The de-icing effect of the nano-copper sulfide de-icing membrane prepared in this embodiment was verified. A 20 μL droplet was added to the surface of the membrane and frozen at -30 °C for 2 h to form ice droplets. Subsequently, photothermal and electrothermal de-icing capabilities were tested at -15 °C. The results are as follows: Figure 7 As shown.
[0047] like Figure 7 As shown, under a light intensity of 1 kW / m², the ice droplets completely melted in 135 s. Under no light and with a 14V voltage applied, the ice droplets completely melted in 86 s. Under the combined effect of photothermal and electrothermal action, they melted completely in only 50 s. This demonstrates that the copper sulfide de-icing film can effectively melt surface ice layers, achieving all-weather de-icing.
[0048] Example 2: Take approximately 60 mL of waste etching solution (with 2 mL of polyethylene glycol added), and add approximately 15 mL of 0.1 g / mL sodium sulfide solution (with 2 mL of polyethylene glycol added) dropwise while stirring. After the addition is complete, continue stirring for 30 min, then let it stand for 40 min. Take 1 mL of the lower black suspension and dilute it to 50 mL with a 1:1 mixture of deionized water and anhydrous ethanol to obtain the diluted solution.
[0049] A 50 mm diameter nylon filter membrane (0.22 μm pore size) was used with a vacuum filtration device for filtration. 10 mL of diluent was added each time, and after filtration, 5 mL of anhydrous ethanol was added for washing. This filtration and washing process was repeated six times to obtain a uniform black film sample. The sample was air-dried at room temperature for 1 hour, then transferred to an oven and dried at 80°C for 2 hours to obtain a nano-copper sulfide film.
[0050] Copper tapes were attached as electrodes on both sides of the obtained copper sulfide nanofilm, with an electrode width of 5 mm and a distance of 15 mm between the two electrodes. A hydrophobic coating of polydimethylsiloxane (PDMS and ethyl acetate diluted at a mass ratio of 1:3) was uniformly sprayed onto the surface of the copper sulfide film, and then cured at 60 °C for 1 hour to complete the encapsulation of the photothermal-electrothermal dual-mode de-icing film.
[0051] Example 3: Take approximately 60 mL of waste etching solution (with 3 mL of polyethylene glycol added), and add approximately 15 mL of 0.1 g / mL sodium sulfide solution (with 2 mL of polyethylene glycol added) dropwise while stirring. After the addition is complete, continue stirring for 20 min, then let it stand for 60 min. Take 1 mL of the lower black suspension and dilute it to 50 mL with a 1:1 mixture of deionized water and anhydrous ethanol to obtain the diluted solution.
[0052] A 50 mm diameter nylon filter membrane (0.1 μm pore size) was used with a vacuum filtration device for filtration. 5 mL of diluent was added each time, and after filtration, 5 mL of anhydrous ethanol was added for washing. This filtration and washing process was repeated 10 times to obtain a uniform black film sample. The sample was air-dried at room temperature for 1 hour, then transferred to an oven and dried at 80°C for 2 hours to obtain a copper sulfide nanofilm.
[0053] Copper tapes were attached as electrodes on both sides of the obtained copper sulfide nanofilm, with an electrode width of 5 mm and a distance of 25 mm between the two electrodes. A hydrophobic coating of polydimethylsiloxane (PDMS and ethyl acetate diluted at a mass ratio of 1:3) was uniformly sprayed onto the surface of the copper sulfide film, and then cured at 60 °C for 2 h to complete the encapsulation of the photothermal-electrothermal dual-mode de-icing film.
[0054] like Figure 8 As shown, a photothermal-electrothermal de-icing membrane for recovering nano-copper sulfide based on waste copper etching solution includes a nylon filter membrane 1 at the bottom, a nano-copper sulfide film 2 on the surface of the nylon filter membrane 1, copper electrodes 3 on both sides of the nano-copper sulfide film 2, and a polydimethylsiloxane hydrophobic coating 4 on the upper end of the nano-copper sulfide film 2. The polydimethylsiloxane hydrophobic coating 4 covers the upper surface of the nano-copper sulfide film 2 and the contact area with the copper electrodes 3.
[0055] The above descriptions are merely some embodiments of the present invention. For those skilled in the art, various modifications and improvements can be made without departing from the inventive concept of the present invention. Therefore, all technical solutions that can be obtained by those skilled in the art based on the inventive concept and through logical analysis, reasoning, or limited experimentation on the basis of existing technology are within the scope of protection of the invention.
Claims
1. A method for preparing a photothermal-electrothermal de-icing film based on the recovery of nano-copper sulfide from waste copper etching solution, characterized in that, Includes the following steps: Step 1: Add sodium sulfide solution dropwise to the waste copper etching solution, stir and let stand to obtain a mixture of reaction products; Step 2: After standing, the upper layer of the mixture is a clear liquid and the lower layer is a suspension; the lower suspension is taken out and diluted with a mixed solvent of deionized water and anhydrous ethanol to obtain a diluted solution; Step 3: Deposit the diluent onto the surface of the nylon filter membrane by vacuum filtration. Add 5-10 mL of diluent each time. After each layer of film is deposited, wash with anhydrous ethanol. After multiple vacuum filtrations and washings, a black film sample is obtained. Step 4: Air-dry the black film sample at room temperature, then bake it to obtain a nano-copper sulfide film; Step 5: Prepare electrodes on both sides of the copper sulfide nanofilm obtained in step 4; Step 6: After shielding and protecting the electrodes on both sides of the nano copper sulfide film obtained in Step 5, a polydimethylsiloxane coating is sprayed onto the surface of the copper sulfide and then cured. After hydrophobic modification, a photothermal-electrothermal de-icing film of nano copper sulfide is obtained. In step 1, polyethylene glycol dispersant is added to the waste copper etching solution, which is derived from the copper manufacturing process in the display panel industry. The sodium sulfide solution used in step 1 is 0.1 g / mL, and the volume ratio of sodium sulfide solution to polyethylene glycol is between 5:1 and 10:
1. In step 1, the volume ratio of waste etching solution to sodium sulfide solution is between 4:1 and 5:
1. In step 4, the drying temperature is 60–80 °C; In step 5, the electrode is made of copper tape; In step 6, the polydimethylsiloxane to be sprayed is diluted with ethyl acetate to a mass ratio of 1:3 to 1:
4. In step 6, the curing temperature is 60-80 ℃ and the curing time is 1-2 h; The photothermal-electrothermal de-icing membrane prepared based on the method for recovering nano-copper sulfide from waste copper etching solution includes a heating element and an electrode, wherein the heating element is a nano-copper sulfide thin film deposited on the surface of a nylon filter membrane; Among them, nano-copper sulfide is recovered from waste copper etching solution; The electrodes are connected to both sides of the copper sulfide nanofilm, forming an electrical connection with the copper sulfide nanofilm, and the middle region of the copper sulfide nanofilm has an exposed portion for receiving sunlight. A polydimethylsiloxane hydrophobic coating is applied to the upper surface of the nano-copper sulfide film and the upper surface of the nano-copper sulfide film at the contact point with the copper electrode. The nano-copper sulfide film utilizes its electrical conductivity and Joule heating effect to achieve electric heating, and can be de-iced by electric heating when an external power source is connected. The photothermal effect of the nano-copper sulfide thin film comes from its local surface plasmon resonance effect and nonradiative relaxation recombination between semiconductor bands, achieving wide-band absorption and high photothermal conversion capability across the entire solar spectrum, enabling photothermal de-icing under sunlight. The photothermal-electrothermal de-icing membrane has two functional modes: electrothermal de-icing and photothermal de-icing. You can choose to operate one of the functional modes or operate the two functional modes in combination to achieve all-weather de-icing. The nano-copper sulfide film is composed of Mixed composition, in which copper element is Mixed valence states exist.
2. The method for preparing a photothermal-electrothermal de-icing film based on waste copper etching solution for recovering nano-copper sulfide, as described in claim 1, is characterized in that... The dilution factor of the diluent in step 2 is 25 to 50 times; In step 3, the nylon filter membrane has a diameter of 50 mm and a pore size of 0.1 μm.
3. The application of the de-icing film prepared according to claim 1 or 2, characterized in that, The de-icing membrane is used for de-icing in one or more scenarios, such as aircraft wings, drone supports, wind turbine blades, or ship decks.
4. The application according to claim 3, characterized in that, The de-icing membrane is fixed to the surface of the object to be de-iced by attaching, bonding or embedding, and can be selected to work in photothermal mode only, electrothermal mode only or dual-mode collaborative operation according to the usage scenario.
Citation Information
Patent Citations
Method for completely recycling acidic copper chloride etching waste liquid through thermal analysis process
CN113460965A
Efficient recycling process based on panel industry copper etching waste liquid
CN121377192A
Flexible anti-icing film with double-strategy intelligent deicing function and preparation method thereof
CN116606463A
Method for preparing plasmon nano copper sulphide from copper-containing waste liquid and photo-thermal application of plasmon nano copper sulphide
CN121342076A